FREQUENCY OF PAIN ASSOCIATED WITH ULTRASOUND GUIDED PERCUTANEOUS LIVER BIOPSY - Akhtar, Mehmood; Ahmad, Munir; Rehman, Abdur (Journal of Postgraduate Medical Institute, 2012)
Objectives: To determine the frequency of pain associated with ultrasound guided percutaneous trucut needle liver biopsy. Methodology: This prospective descriptive study was conducted in Radiology Department, Lady Reading Hospital Peshawar over a period of six months from April 2009 to October 2009. Cases were referred from wards as well as OPD. Patients of ages between 14 and 75 years (48.42+9.91), having diffuse or focal hepatic solid lesion (s) seen on ultrasound abdomen, were included and patients with pregnancy, moderate to marked ascites, abnormal PT and/or APTT even after correction, thrombocytopenia, coagulopathy and those using anticoagulants were excluded from the study. After informed written consent, procedure was done and data analyzed. Results: Out of 52 procedures, pain occurred in 42 (80.8 %) cases. Mild to moderate pain occurred in 41 (78.8%) cases whereas severe pain was observed in 1 patient (1.9%). Frequency of pain was more in females (14/15=93.4%) than males (28/37=75.7%). Frequency of pain was more in subcostal (18/21=85.8%) than intercostal (24/31=77.4%) approach. 27 of 33 (81.8%) patients with focal solid hepatic lesion and 15 of 19 (78.9%) patients with diffuse hepatic disease reported pain. Conclusion: Percutaneous ultrasound-guided liver biopsy is associated with low frequency of severe pain. This study shows that females report pain more frequently than males. The incidence of biopsy associated pain is more in patients who are addicted to narcotics.